A 3D‐Printed, Freestanding Carbon Lattice for Sodium Ion Batteries - Katsuyama, Yuto; Kudo, Akira; Kobayashi, Hiroaki; Han, Jiuhui; Chen, Mingwei; Honma, Itaru; Kaner, Richard B. (Small (Weinheim an der Bergstrasse, Germany), 2022)
Increasing mass loadings of battery electrodes critically enhances the energy density of an overall battery by eliminating much of the inactive components, while compacting the battery size and lowering the costs of the ingredients. A hard carbon microlattice, digitally designed and fabricated by stereolithography 3D‐printing and pyrolysis, offers enormous potential for high‐mass‐loading electrodes. In this work, sodium‐ion batteries using hard carbon microlattices produced by an inexpensive 3D printer are demonstrated. Controlled periodic carbon microlattices are created with enhanced ion transport through microchannels. Carbon microlattices with a beam width of 32.8 µm reach a record‐high areal capacity of 21.3 mAh cm−2 at a loading of 98 mg cm−2 without degrading performance, which is much higher than the conventional monolithic electrodes (≈5.2 mAh cm−2 at 92 mg cm−2). Furthermore, binder‐free, pure‐carbon elements of microlattices enable the tracking of structural changes in hard carbon that support the hypothesized intercalation of ions at plateau regions by temporal ex situ X‐ray diffraction measurements. These results will advance the development of high‐performance and low‐cost anodes for sodium‐ion batteries as well as help with understanding the mechanisms of ion intercalations in hard carbon, expanding the utilities of 3D‐printed carbon architectures in both applications and fundamental studies. A record‐high areal capacity (21.3 mAh cm−2) for sodium‐ion battery carbon anodes is achieved by a 3D‐printed carbon microlattice with an extraordinary high‐mass‐loading (98 mg cm−2). Furthermore, binder‐free, pure‐carbon elements of microlattice enable the tracking of structural changes in hard carbon during charge/discharge, supporting the hypothesized intercalation of ions at plateau regions by ex situ X‐ray diffraction measurements.